Mixed Gender High Performance Optimization (HPO) Teams: The Roles of Adult Learning Theories in the Enhancement of Endurance Teams’ Capabilities - Constance Carpenter (Adult Education Research Conference, 2017)
High performance optimization endurance teams perform complex tasks requiring rapid decision making under chaotic conditions. The discussion explores the application of theoretical foundations when planning adult education programs for teams.
Keywords: high performance optimization; endurance teams